(3Sff GHf eGLgs - (3GHf eGLI , eMeO Hf jRjO Hf GdQHYj GdbRhjfj, CHh YHO Gddg,GHf eGLg,J (B273 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdSfI HGH EJHGY SfI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3jfJgi HaUd UaI GdfGQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B115s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1004s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs